Diagnostics and the neglected tropical diseases roadmap: setting the agenda for 2030. (9th November 2020) - Souza, Ashley A; Ducker, Camilla; Argaw, Daniel; King, Jonathan D; Solomon, Anthony W; Biamonte, Marco A; Coler, Rhea N; Cruz, Israel; Lejon, Veerle; Levecke, Bruno; Marchini, Fabricio K; Marks, Michael; et al.
Abstract: Accurate and reliable diagnostic tools are an essential requirement for neglected tropical diseases (NTDs) programmes. However, the NTD community has historically underinvested in the development and improvement of diagnostic tools, potentially undermining the successes achieved over the last 2 decades. Recognizing this, the WHO, in its newly released draft roadmap for NTD 2021–2030, has identified diagnostics as one of four priority areas requiring concerted action to reach the 2030 targets. As a result, WHO established a Diagnostics Technical Advisory Group (DTAG) to serve as the collaborative mechanism to drive progress in this area. Here, the purpose and role of the DTAG are described in the context of the challenges facing NTD programmes.